2007
DOI: 10.1021/bi701014y
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Characterization of an Integrin-Targeted Lipopolyplex Gene Delivery Vector

Abstract: Nonviral gene delivery vectors now show good therapeutic potential: however, detailed characterization of the composition and macromolecular organization of such particles remains a challenge. This paper describes experiments to elucidate the structure of a ternary, targeted, lipopolyplex synthetic vector, the LID complex. This consists of a lipid component, Lipofectin (L) (1:1 DOTMA:DOPE), plasmid DNA (D), and a dual-function, cationic peptide component (I) containing DNA condensation and integrin-targeting s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
57
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 59 publications
5
57
0
Order By: Relevance
“…17 In the present study, we found that the transfection efficiency of HLPD is closely related to the inserted spacer of the multifunctional peptides, between KRPTMRFRYTWNPMK and R 16 . Thus, we investigated the effect of spacer element on the in vitro DNA transfection of HLPD and mainly explored the characteristics and internalization mechanism of HLPD containing the peptides with different spacers between KRPTMRFRYTWNPMK and R 16 . The cell uptake and gene expression of Q-complexes after incubation with different inhibitors were analyzed to validate the successful intracellular gene delivery pathway.…”
supporting
confidence: 53%
See 4 more Smart Citations
“…17 In the present study, we found that the transfection efficiency of HLPD is closely related to the inserted spacer of the multifunctional peptides, between KRPTMRFRYTWNPMK and R 16 . Thus, we investigated the effect of spacer element on the in vitro DNA transfection of HLPD and mainly explored the characteristics and internalization mechanism of HLPD containing the peptides with different spacers between KRPTMRFRYTWNPMK and R 16 . The cell uptake and gene expression of Q-complexes after incubation with different inhibitors were analyzed to validate the successful intracellular gene delivery pathway.…”
supporting
confidence: 53%
“…The HA coated at the surface of ternary complexes is in charge of shielding the negative charge of the nanoparticle surface, as well as the oriented binding to the tumor tissues and cells because HA actively targets receptors (such as CD44) distributed on the surfaces of the tumor cells. 14,15 From the similar reported formulation, 16 we could conclude that some of KRPTMRFRYTWNPMK in the multifunctional peptide protruded at the surface of LPD, which possibly induces the nanoparticles to penetrate into the tumor cells, and the lipid component destroys the endosomal membranes through membrane fusion function of DOPE. 17 In the present study, we found that the transfection efficiency of HLPD is closely related to the inserted spacer of the multifunctional peptides, between KRPTMRFRYTWNPMK and R 16 .…”
mentioning
confidence: 66%
See 3 more Smart Citations